INTERPRETASI KATA AL-á¹¢IRÃ‚á¹¬ AL-MUSTAQÃŽM DALAM ALQURAN: APLIKASI SEMANTIK TOSHIHIKO IZUTSU - Muhammad Anwar Idris (UIN Siber Syekh Nurjati Cirebon, 2020)
This paper tries to reveal the meaning of the word al-á¹¢irÃ¢á¹Â al-MustaqÃ®m . As for the word al-á¹¢irÃ¢á¹ al-MustaqÃ®m and its derivations; as many as 33 well-known words in 21 surah in the Alquran. Of the many mentions of this word in the Quran, of course, it will have a different meaning. So it is necessary to study what exactly the meaning of al-á¹¢irÃ¢á¹Â al-MustaqÃ®m in Alquran using the semantic theory of Toshihiko Izutsu. This theory explains the existence of the basic meaning and relational meaning of Pragmatics and paradigmatics and Weltanschauung (world of meaning) al-á¹¢irÃ¢á¹ Â al-MustaqÃ®m. The results of this study, that the word al-á¹¢irÃ¢á¹Â al-MustaqÃ®m in Alquran has the basic meaning of